2021
DOI: 10.21203/rs.3.rs-412802/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist as a weaning mode for adults with invasive mechanical ventilation: a systematic review and meta-analysis

Abstract: Background Prolonged ventilatory support is associated with poor clinical outcomes. Partial support modes, especially pressure support ventilation, are frequently used in clinical practice but are associated with patient-ventilation asynchrony and deliver fixed levels of assist. Neurally adjusted ventilatory assist (NAVA), a mode of partial ventilatory assist that reduces patient-ventilator asynchrony (PVA), may be an alternative for weaning. However, the effects of NAVA on weaning outcomes in clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…This implies that an updated system should trigger from a signal related to expiration as opposed to the beginning of inspiration. Some neuromuscular signals, such as the electrical activity of the diaphragm (Edi), contain detailed information about both inspiration and expiration times 35,36 . Edi amplitude is also proportional to the neural drive, as well as the degree of contraction of the diaphragmatic muscle, therefore opening up the possibility of adaptive control.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that an updated system should trigger from a signal related to expiration as opposed to the beginning of inspiration. Some neuromuscular signals, such as the electrical activity of the diaphragm (Edi), contain detailed information about both inspiration and expiration times 35,36 . Edi amplitude is also proportional to the neural drive, as well as the degree of contraction of the diaphragmatic muscle, therefore opening up the possibility of adaptive control.…”
Section: Contributionsmentioning
confidence: 99%
“…Triggering from Edi measured at the oesophageal level via a feeding tube 37 may be warranted to improve mechanical ventilation. This method, known as neurally adjusted ventilatory assist, is available in the clinical setting with mechanical ventilation and may improve respiratory weaning of patients that are challenging to wean 36 . The same principle could be applied to our diaphragm-assist system; using a more upstream signal with greater information on the native respiratory effort would allow for a more robust control system.…”
Section: Contributionsmentioning
confidence: 99%
“…A 2021 meta-analysis of seven trials (n ¼ 693) indicated that patients managed with NAVA had a higher liberation success rate, shorter duration of mechanical ventilation, lower hospital mortality rate, and more VFDs than those managed with other partial support modes. 71 Adaptive Support Ventilation Dr. Fleur Tehrani, an electrical engineering professor, invented and patented ASV in 1991. 72 It is based on the physiologic principles described by Otis et al 73 and Mead 74 that for a given alveolar ventilation, there is a specific combination of RR and Vt that achieves the lowest work of breathing to minimize the effects of elastic and resistive load on the respiratory system.…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…A 2021 meta-analysis of seven trials ( n = 693) indicated that patients managed with NAVA had a higher liberation success rate, shorter duration of mechanical ventilation, lower hospital mortality rate, and more VFDs than those managed with other partial support modes. 71…”
Section: Newer Modes Used During Liberation From Mechanical Ventilationmentioning
confidence: 99%
“…However, it also indicated that the advantages of NAVA over PSV were smaller when PSV was carefully set avoiding excessive support 25 . A systematic review suggests that the NAVA mode may improve the rate of weaning success compared with other partial support modes for difficult-to-wean individuals 26 .…”
Section: Ventilatory Strategies In Pmvmentioning
confidence: 99%